2016
DOI: 10.1111/jnc.13688
|View full text |Cite
|
Sign up to set email alerts
|

Rho‐associated protein kinase 1 (ROCK1) is increased in Alzheimer's disease and ROCK1 depletion reduces amyloid‐β levels in brain

Abstract: Alzheimer’s disease (AD) is the leading cause of dementia and mitigating amyloid-β (Aβ) levels may serve as a rational therapeutic avenue to slow AD progression. Pharmacologic inhibition of the Rho-associated protein kinases (ROCK1 and ROCK2) is proposed to curb Aβ levels, and mechanisms that underlie ROCK2’s effects on Aβ production are defined. How ROCK1 affects Aβ generation remains a critical barrier. Here, we report that ROCK1 protein levels were elevated in mild cognitive impairment due to AD (MCI) and A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
75
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(83 citation statements)
references
References 26 publications
7
75
0
1
Order By: Relevance
“…APP shedding is directly mediated by α- and β-secretase generating either non-amyloidogenic (sAPPα) or amyloidogenic fragments (Tang, 2005). Our data show that ROCK1 activation enhances the amyloidogenic pathway, consistent with recent data (Henderson et al, 2016). However, we demonstrate that ROCK1 decreased sAPPα shedding in cultured cells, but also reduced rather than increased Aβ secretion from the cells, suggesting that ROCK1 may also play a role in Aβ secretion at the plasma membrane (potentially associated with the aberrant phosphorylation of Aβ, see above).…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…APP shedding is directly mediated by α- and β-secretase generating either non-amyloidogenic (sAPPα) or amyloidogenic fragments (Tang, 2005). Our data show that ROCK1 activation enhances the amyloidogenic pathway, consistent with recent data (Henderson et al, 2016). However, we demonstrate that ROCK1 decreased sAPPα shedding in cultured cells, but also reduced rather than increased Aβ secretion from the cells, suggesting that ROCK1 may also play a role in Aβ secretion at the plasma membrane (potentially associated with the aberrant phosphorylation of Aβ, see above).…”
Section: Discussionsupporting
confidence: 94%
“…Two constitutively-expressed ROCK enzymes have been identified—ROCK1 and ROCK2 that share 92% homology in their kinase domain and differ most in their regulatory domains and subcellular localization (Ishizaki et al, 1997; Shi et al, 2013; Chong et al, 2016). Recent studies show that ROCK1 modulates the shedding of the α-secretase-cleaved soluble APP ectodomain (sAPPα) from cultured cells, and that ROCK1 depletion reduces the levels of Aβ (Herskowitz et al, 2013; Henderson et al, 2016). The buildup of internal Aβ rather than its external deposition is associated with neuronal loss in APP/PS1 knock-in mice suggesting externalization of cellular Aβ is protective (Christensen et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…; Henderson et al . ). Additionally, in both rodent models and AD patients, both isoforms are elevated in the brain (Herskowitz et al .…”
Section: Therapeutic Considerations Of Rock1/rock2 Inhibitionmentioning
confidence: 97%
“…We showed that the oAβ [25][26][27][28][29][30][31][32][33][34][35] injection-induced inhibition of sAPPα and ADAM10 is associated with an activation of ROCK/PDK1 pathways. 68,75,76 ROCK activity seems to be directly upregulated by GC, 72,73,77 and ROCK/PDK1 activation after oAβ [25][26][27][28][29][30][31][32][33][34][35] is reversed by treatment with CORT113176, again constituting a vicious cycle based on feed-forward effects on GR signaling (Figure 7). 68,75,76 ROCK activity seems to be directly upregulated by GC, 72,73,77 and ROCK/PDK1 activation after oAβ [25][26][27][28][29][30][31][32][33][34][35] is reversed by treatment with CORT113176, again constituting a vicious cycle based on feed-forward effects on GR signaling …”
Section: F I G U R Ementioning
confidence: 99%